Evaluation of Species Invasiveness: A Case Study with Acacia dealbata Link. on the Slopes of Cabeça (Seia-Portugal) - Raposo, Mauro (2021)
One of the main causes of biodiversity loss in the world is the uncontrolled expansion of invasive plants. According to the edaphoclimatic conditions of each region, plants acquire different invasion behaviors. Thus, to better understand the expansion of invasive plants with radial growth, it is proposed to use two equations, the Annual Linear Increment (ALI) and the Annual Invasiveness Rate (AIR). These equations are applied using spatiotemporal data obtained from the analysis of orthophotomaps referring populations of Acacia dealbata Link. in areas located in Serra da Estrela, Portugal. As a result, the area occupied by this species in the parish of Cabeça was evaluated and a 20-year projection was carried out. The data produced by these equations contributed to improving the knowledge about the invasion behavior of exotic species in a rigorous and detailed way according to local ecological conditions. This study may serve as the basis for the application of other similar situations concerning invasive species in other territories, to improve the efficiency of future projections for these species. Local technical and scientific knowledge will contribute to improving spatial and management planning, enabling a better adequacy and effectiveness of the control measures to be adopted.